2017
DOI: 10.1177/0022034517732538
|View full text |Cite
|
Sign up to set email alerts
|

Ciliopathy Protein Tmem107 Plays Multiple Roles in Craniofacial Development

Abstract: A broad spectrum of human diseases called ciliopathies is caused by defective primary cilia morphology or signal transduction. The primary cilium is a solitary organelle that responds to mechanical and chemical stimuli from extracellular and intracellular environments. Transmembrane protein 107 (TMEM107) is localized in the primary cilium and is enriched at the transition zone where it acts to regulate protein content of the cilium. Mutations in TMEM107 were previously connected with oral-facial-digital syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 33 publications
(50 reference statements)
4
33
0
Order By: Relevance
“…The phenotype was rescued by overexpression of Smad1 ( Ap2a IRESCre / + ;COET;Fsmad1 ).CLO or CLP33 Tfap2a transcription factor AP-2, alpha[42]25381013 Tfap2a null/neo mice show bilateral CL and CP at 100%.CLP34 Tgfbr1 (aka Alk5) transforming growth factor, beta receptor I[43]18586087 Nestin-Cre;Tgfbr1 cKO mice show either unilateral or bilateral CL at 64%. No information about CP.CLO or CLP35 Tmem107 transmembrane protein 107[44, 45]22698544; 28954202Homozygous mutant mice show CL and CP at 14%.CLP36 Trp53 transformation related protein 53[46]25119037 CMV-Cre;Trp53 LSL-25.26.53.54/+ mice show CL and CP.CLP37 Trp63 transformation related protein 63[47]18634775Homozygous null mutant mice show bilateral CL and CP at 100%.CLP38 Wdr19 (aka Ift144) WD repeat domain 19[48]22228095Homozygous mutant mice show bilateral CL and CP. Mutation is ENU-induced single point mutation.CLP39 Wnt9b wingless-type MMTV integration site family, member 9B[49]21982646 Foxg1-Cre /+ ;Wnt9b cKO mice show bilateral CL at 59% and CP.CLO or CLPCLO, cleft lip only; CLP, cleft lip and cleft palate; CPO, cleft palate only…”
Section: Resultsmentioning
confidence: 99%
“…The phenotype was rescued by overexpression of Smad1 ( Ap2a IRESCre / + ;COET;Fsmad1 ).CLO or CLP33 Tfap2a transcription factor AP-2, alpha[42]25381013 Tfap2a null/neo mice show bilateral CL and CP at 100%.CLP34 Tgfbr1 (aka Alk5) transforming growth factor, beta receptor I[43]18586087 Nestin-Cre;Tgfbr1 cKO mice show either unilateral or bilateral CL at 64%. No information about CP.CLO or CLP35 Tmem107 transmembrane protein 107[44, 45]22698544; 28954202Homozygous mutant mice show CL and CP at 14%.CLP36 Trp53 transformation related protein 53[46]25119037 CMV-Cre;Trp53 LSL-25.26.53.54/+ mice show CL and CP.CLP37 Trp63 transformation related protein 63[47]18634775Homozygous null mutant mice show bilateral CL and CP at 100%.CLP38 Wdr19 (aka Ift144) WD repeat domain 19[48]22228095Homozygous mutant mice show bilateral CL and CP. Mutation is ENU-induced single point mutation.CLP39 Wnt9b wingless-type MMTV integration site family, member 9B[49]21982646 Foxg1-Cre /+ ;Wnt9b cKO mice show bilateral CL at 59% and CP.CLO or CLPCLO, cleft lip only; CLP, cleft lip and cleft palate; CPO, cleft palate only…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the mouse has been shown to provide a good model for numerous ciliopathies and these models have begun to elucidate the underlying mechanisms of these diseases (18)(19)(20)(21). Furthermore, there is evidence to suggest that murine ciliopathy phenotypes are influenced by genetic modifiers.…”
mentioning
confidence: 99%
“…This is consistent with the results of Christopher et al and Cela et al where TMEM107 deletion inhibited differentiation and promoted migration of neuronal stem cells in mouse embryos. 15,16 The invasiveness of NSCLC has been shown to be related to the acquisition of EMT. 9 We found that TMEM107 knockdown made A549 and H460 cells lose Ecadherin and gain N-cadherin and vimentin which are important symbols of occurrence of EMT, 28 suggesting a novel mechanism underlying the involvement of TMEM107 in invasion of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] TMEM107 is a relatively newly identified gene which encodes for transmembrane protein 107 (TMEM107), which is localized at the transition zone of the primary cilium and regulates the development and protein content of the cilium. [15][16][17][18][19][20] Fibroblasts from patients with mutations in TMEM107 showed a reduced number of cilia, altered cilia length, and impaired Hedgehog signaling in several studies. [17][18][19] Christopher et al and Cela et al confirmed that TMEM107 deletion could cause significant dysfunction of the Hedgehog signaling pathway in mice, which in turn affects the differentiation and migration of their embryonic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation